2000
DOI: 10.1302/0301-620x.82b5.10183
|View full text |Cite
|
Sign up to set email alerts
|

The role of coagulation abnormalities in the development of Perthes' disease

Abstract: Recent reports have suggested an association between Perthes' disease and an underlying thrombophilic or hypofibrinolytic tendency. In Northern Ireland there is a high incidence of Perthes' disease (11.7 per 100,000 or 1 in 607 children) in a stable paediatric population. We reviewed 139 children with Perthes' disease and compared them with a control group of 220 aged- and gender-matched healthy primary schoolchildren with similar racial and ethnic backgrounds. There were no significant deficiencies of antithr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…7 Our results, in agreement with the reports of others, do not support the hypothesis that there is a primary role for inherited thrombophilia in the pathogenesis of Perthes' disease. [17][18][19][20] We did, however, detect four patients who were homozygous mutants among our five with Activated Protein C-resistance due to Factor V Leiden mutations. In these four patients the disease ran an extremely severe course.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…7 Our results, in agreement with the reports of others, do not support the hypothesis that there is a primary role for inherited thrombophilia in the pathogenesis of Perthes' disease. [17][18][19][20] We did, however, detect four patients who were homozygous mutants among our five with Activated Protein C-resistance due to Factor V Leiden mutations. In these four patients the disease ran an extremely severe course.…”
Section: Discussionmentioning
confidence: 62%
“…Further investigations in Europe, including the most extensive study, did not agree with Glueck et al 7 concerning the role of thrombophilia. [18][19][20] In our study, 47 patients were investigated in order to determine the role of thrombogenic factors in the evolution of Perthes' disease. The haemostatic parameters did not differ significantly from those in the control group, except for a slightly decreased plasminogen level, which we did not think could play a significant role in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[22] While some studies have found an increased rate of abnormalities of coagulation in the patients with LCPD, [21,22,56,59,60] others have not found any association at all. [61][62][63][64] The discrepancy might be due to some confounding factors, including a small sample size in some studies, the retrospective study design, use of suboptimal controls, and non-standardized range of laboratory values for coagulation factor level. As far as prospective studies are concerned, a random series of 50 consecutive LCPD patients did not show a difference in the prevalence of antithrombin III, protein-S, or protein-C deficiencies between the group of LCPD patients and the estimated frequency of disease in the population.…”
Section: Coagulation Factors and Lcpdmentioning
confidence: 99%
“…Thrombophilia is one of the most widely accepted since the tendency to develop states of hypercoagulability could lead to the Open Access *Correspondence: edgarhz1969@yahoo.com.mx; elbareyesm@gmail.com † José Guillermo Buendía Pazarán, Edgar Hernández Zamora and Armando O. Rodríguez-Olivas have contributed equally to this work 1 Morphology Department, Escuela Nacional de Ciencias Biológicas, Instituto Politécnico Nacional (ENCB, IPN), Prolongación de Carpio y Plan de Ayala s/n, Col. Santo Tomás, Miguel Hidalgo, C.P. 11340 Mexico City, Mexico 2 Genomic Medicine, Instituto Nacional de Rehabilitación "Luis Guillermo Ibarra" (INR-LGII), Mexico City, Mexico development of necrosis [4][5][6]. On the other hand, described collagen gene alterations could also be related to the etiology of the disease [7].…”
Section: Introductionmentioning
confidence: 99%